Fabrication of Microstructures on RB-SiC by Ultrasonic Cavitation Assisted Micro-Electrical Discharge Machining - Liew , Pay Jun; Shimada, Keita; Mizutani, Masayoshi; Yan , Jiwang; Kuriyagawa, Tsunemoto (2013)
Ultrasonic cavitation assisted micro-electrical discharge machining was used to fabricate microstructures on reaction-bonded silicon carbide. To aid the removal of debris from the machining gap and to obtain a good surface finish, carbon nanofibers were added into the dielectric fluid. The suspension of carbon nanofibers in the dielectric fluid and the cavitation bubble effect induced by the vibration of the dielectric fluid proved to be effective in reducing the deposition of tool material on the workpiece surface. The tool material deposition rate was found to be significantly affected by the vibration amplitude and the distance between the oscillator and the workpiece. With a hemispherical electrode and inclined workpiece, high accuracy micro-dimples could be obtained within a short time. A nanometer-level surface finish was successfully obtained on a hard-brittle RB-SiCmoldmaterial.